Design and Structural Analysis of Aromatic Inhibitors of Type II Dehydroquinase from Mycobacterium tuberculosis. Issue 1 (18th September 2014) - Howard, Nigel I.; Dias, Marcio V. B.; Peyrot, Fabienne; Chen, Liuhong; Schmidt, Marco F.; Blundell, Tom L.; Abell, Chris
Abstract 3‐Dehydroquinase, the third enzyme in the shikimate pathway, is a potential target for drugs against tuberculosis. Whilst a number of potent inhibitors of the Mycobacterium tuberculosis enzyme based on a 3‐dehydroquinate core have been identified, they generally show little or no in vivo activity, and were synthetically complex to prepare. This report describes studies to develop tractable and drug‐like aromatic analogues of the most potent inhibitors. A range of carbon–carbon linked biaryl analogues were prepared to investigate the effect of hydrogen bond acceptor and donor patterns on inhibition. These exhibited inhibitory activity in the high‐micromolar range. The addition of flexible linkers in the compounds led to the identification of more potent 3‐nitrobenzylgallate‐ and 5‐aminoisophthalate‐based analogues.